Optoelectric Properties of Thermally Evaporated ClAlClPc Thin Films - Raji Koshy; C.S. Menon (Журнал нано- та електронної фізики)
Vacuum sublimed thin films of Chloro Aluminium Chloro phthalocyanine were prepared at room temperature onto glass substrates at a base pressure of 10 -5 Torr. Annealing was done in air and the effect of annealing temperature on the optical and electrical properties were studied. Optical absorption spectra of films annealed at temperatures, 373 K, 423 K, 473 K and as-deposited were taken over a wavelength range of 200 to 900 nm and the optical energy band gap Eg and the onset and excitonic energy gap were calculated. It is found that Eg slightly increases with increase in air annealing temperature and excitonic energy gap has practically unchanged. Arrhenius plot yields thermal activation energy in the intrinsic region and impurity scattering region. The variation in the electrical properties with air annealing temperature were also studied and activation energy was determined. Thermal activation energy is calculated from the Arrhenius plot in the intrinsic and extrinsic regions, it is found that it decreases with increase in the air annealing temperatures.